THE COMMODIFICATION OF MURALS - Putra, I Gede Jaya; Budayana, I Wayan Gede; Dwinatta, Aldy Karunia (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2020)
This article discusses the commodification of murals in terms of their development, which is a strategy for tourism sustainability in Bali. The mural is considered one of the aesthetic dishes, to show the exoticism of Bali. Based on field observations with the Seminyak area as an observation location, there are many murals that support the exterior and interior spaces, as a selfie area and also devoted as a photobooth to attract tourists. The study focuses on the commodification and degradation of murals, by examining the presence of new meanings that are in line with the development of tourism and the arts in society. Sources of data obtained through a qualitative approach using descriptive analysis and observation methods. The theory used is the Baudrillard Commodification, semiotics by Charles Sanders Peirce in the form of representations, objects and interpretations to understand the signs in the mural. As well as aesthetic theory to see the distinguishing power of the presence of murals that enliven the tourism scene. The study shows the current mural position that is intertwined between art and tourism as well as the position of art and tourists. Murals in Bali have now adopted a new survival system. By bringing all forms of beauty as bargaining power, instead of attracting the interests of tourists and local people, to force themselves to be read through new perspectives by adapting a positiveistic realm.